Validation of burnout prevention module elements for informal caregivers of depressed individuals: Fuzzy Delphi Method - Syafiqa Hazira; Rozainee Khairudin; Mohd Akif Farhan Ahmad Basri (Penerbit Universiti Kebangsaan Malaysia, 2025)
Informal caregivers (ICGs) provide vital support to individuals in need, yet they often go unnoticed by the formal healthcare system. While caring for depressed loved ones can be rewarding, it poses significant physical, emotional, and social challenges for ICGs. This research aims to identify key elements for a burnout prevention module for ICGs of individuals with depression using a mobile application. The Fuzzy Delphi Method (FDM) was employed to obtain expert consensus on the module's content. A questionnaire, developed from literature reviews and interviews with eight ICGs, was distributed to ten experts who rated their agreement on each element using a 7-point Likert scale. Nineteen elements met the FDM requirements, which included a threshold value of ≤ 0.2, an expert consensus percentage of ≥ 75%, and an average score of the Fuzzy number exceeding 0.5. The identified elements encompass the module's objective, significance, and duration; symptoms and effects of depression; available interventions; introduction to emotions; breathing techniques; mindfulness and spiritual practice; effective communication; nonverbal communication; active listening; nonjudgmental communication; self-care and stress reduction practices; prioritization; introduction to burnout; coping techniques: STOP method; burnout prevention; self-stigma: be mindful of negative self-talk; social support systems; informal caregiver support groups in Malaysia; and seeking professional help for personal well-being. These elements will serve as a framework for future module development, ultimately enhancing ICGs' well-being and enabling better care.